AERODYNAMICS PARTIALLY CLOSED RECEPTACLE SPACE HIGH–SPEED TRAINS - Kravets, V. V.; Kravets, E. V. (Science and Transport Progress, 2005)
The influence of aerodynamic processes on resistance of intercarload space at change of a configuration of its protection and increase of speed of movement of a train is considered.